If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3n)(4n) = 0 Remove parenthesis around (3n) 3n(4n) = 0 Remove parenthesis around (4n) 3n * 4n = 0 Reorder the terms for easier multiplication: 3 * 4n * n = 0 Multiply 3 * 4 12n * n = 0 Multiply n * n 12n2 = 0 Solving 12n2 = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '12'. n2 = 0 Simplifying n2 = 0 Take the square root of each side: n = {0}
| 2(n-3)=7k+4 | | 10x-2-5x=3x+3 | | Y=5(14)+30 | | 2x+4y=5forx | | 2x^2-10x-2100=0 | | M+15=65 | | y-9-2=5 | | 3x-8=4x-2 | | 3k^2+13k+10= | | .05x-.8=6.7 | | -h=-h+5 | | 3(4x+6)=15x+5-3x+13 | | 3x-4-2x=2x-7 | | 2x+4x^2-8x^3= | | 15+2(3x+2)=3(7+2x) | | 4-4a=36 | | x^4-x^3-9x^2+3x-18=0 | | x-8x+12=23 | | 45=-5X-54 | | 95-m=72 | | 27=15+x+9 | | Y=-7(9)+8 | | a(2a+4b)= | | 7r^2+5r-2=0 | | p+21=15 | | 86=13x-5 | | 5x-123+8x=98 | | -10x+58=6x+41 | | 2x+3(x-3)=6x+1 | | 7-7(5m+2)=-147 | | 91=5x-24 | | 42+f=62 |